2010
DOI: 10.1007/s00213-010-1823-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modafinil and methylphenidate on visual attention capacity: a TVA-based study

Abstract: This is the first pharmacological investigation demonstrating the usefulness of a TVA task for high-resolution and repeated cognitive parameter estimation after cognitive-enhancing medication. Our results confirm previous findings of attentional capacity improvements in low performers and extend the baseline dependency model to methylphenidate. Plasma level-dependent effects of psychostimulants can be modelled on an inverted U-shaped dose-response relationship, which is highly relevant to predict cognitive enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
93
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 82 publications
(101 reference statements)
14
93
1
1
Order By: Relevance
“…The greater impact of modafinil on learning performance in the MA group than in healthy control subjects is consistent with previous observations that individuals who perform poorly on cognitive tasks, relative to those who perform well, show greater improvement after receiving modafinil (Finke et al, 2010; Kalechstein et al, 2010; Spence Figure 2 Task-related fMRI activity (all trials) corresponding to the interaction of treatment and group. The MA group showed a greater response to modafinil than did the control group in the anterior cingulate, bilateral anterior insula/ventrolateral prefrontal cortex, right inferior frontal gyrus, orbito-frontal cortex, and striatum (interaction: MA(modafinilplacebo)4control(modafinil-placebo), see Table 3 for the full list of regions).…”
Section: Discussionsupporting
confidence: 88%
“…The greater impact of modafinil on learning performance in the MA group than in healthy control subjects is consistent with previous observations that individuals who perform poorly on cognitive tasks, relative to those who perform well, show greater improvement after receiving modafinil (Finke et al, 2010; Kalechstein et al, 2010; Spence Figure 2 Task-related fMRI activity (all trials) corresponding to the interaction of treatment and group. The MA group showed a greater response to modafinil than did the control group in the anterior cingulate, bilateral anterior insula/ventrolateral prefrontal cortex, right inferior frontal gyrus, orbito-frontal cortex, and striatum (interaction: MA(modafinilplacebo)4control(modafinil-placebo), see Table 3 for the full list of regions).…”
Section: Discussionsupporting
confidence: 88%
“…The effects of expectations and alertness on performance are not modelled explicitly by TVA [1] or NTVA [2,21] in their present forms, but in recent years a few studies [4,6,7,34] have directly investigated the relationship between these intensity aspects of attention and TVA-based measures of visual selectivity and capacity. Matthias et al [7] investigated the effects of a phasically alerting cue on perceptual processing capacity and spatial attention in three whole report experiments.…”
mentioning
confidence: 99%
“…In addition, the studies show that there are little differences in terms of cognitive-enhancement even compared to placebo: one study [152] even showed a better cogni tive improvement in the placebo group. In addition, many of the CE drugs are most effective only on patients characterized by the lowest baseline of cognitive performance [153][154][155][156][157], while even impairing performance of patients with high baseline cognitive function [154,[158][159][160][161].…”
Section: Summary Of Desired Effects and Side Effects Of Drugs For Cementioning
confidence: 99%